Insights into Alkaline Phosphatase Anti-Inflammatory Mechanisms - Larissa Balabanova; Georgii Bondarev; Aleksandra Seitkalieva; Oksana Son; Liudmila Tekutyeva (Biomedicines)
Background: The endogenous ecto-enzyme and exogenously administered alkaline phosphatase (ALP) have been evidenced to significantly attenuate inflammatory conditions, including Toll-like receptor 4 (TLR4)-related signaling and cytokine overexpression, barrier tissue dysfunction and oxidative stress, and metabolic syndrome and insulin resistance, in experimental models of colitis, liver failure, and renal and cardiac ischemia-reperfusion injury. This suggests multiple mechanisms of ALP anti-inflammatory action that remain to be fully elucidated. Methods: Recent studies have contributed to a deeper comprehension of the role played by ALP in immune metabolism. This review outlines the established effects of ALP on lipopolysaccharide (LPS)-induced inflammation, including the neutralization of LPS and the modulation of purinergic signaling. Results: The additional mechanisms of anti-inflammatory activity of ALP observed in different pathologies are proposed. Conclusions: The anti-inflammatory pathways of ALP may include a scavenger receptor (CD36)-mediated activation of β-oxidation and oxidative phosphorylation, caveolin-dependent endocytosis, and selective autophagy-dependent degradation.